2020
DOI: 10.1371/journal.pone.0233724
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of five steroids and in dried blood spots for newborn screening and retrospective diagnosis of congenital adrenal hyperplasia

Abstract: Congenital adrenal hyperplasia (CAH) is a severe inherited disorder of cortisol biosynthesis that is potentially lethal or can seriously affect quality of life. For the first time, we aimed to assess the stability of 21-deoxycortisol (21Deox), 11-deoxycortisol (11Deox), 4-androstenedione (4AD), 17-hydroxyprogesterone (17OHP) and cortisol (Cort), diagnostic for CAH, in dried blood spots (DBSs) during a 1 year storage at different temperatures. Spiked DBS samples were stored at room temperature, 4˚C, -20˚C or -7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Second, most of the carcasses we sampled had been exposed to ambient conditions for weeks or months prior to being sampled, and samples were stored in paper envelopes for months between sampling and assaying. Although cortisol bound in hair is likely stable on the scale of years to decades (Webb et al 2010, cortisol exogenous to hair would significantly degrade over weeks to months (Grecsó et al 2020). We concluded the high specificity of the cortisol assay and the unlikelihood of exogenous cortisol were sufficient to produce quality data without risking loss of endogenous cortisol through washing.…”
Section: Cortisol Extraction and Enzyme Immunoassaymentioning
confidence: 89%
“…Second, most of the carcasses we sampled had been exposed to ambient conditions for weeks or months prior to being sampled, and samples were stored in paper envelopes for months between sampling and assaying. Although cortisol bound in hair is likely stable on the scale of years to decades (Webb et al 2010, cortisol exogenous to hair would significantly degrade over weeks to months (Grecsó et al 2020). We concluded the high specificity of the cortisol assay and the unlikelihood of exogenous cortisol were sufficient to produce quality data without risking loss of endogenous cortisol through washing.…”
Section: Cortisol Extraction and Enzyme Immunoassaymentioning
confidence: 89%
“…Recently, a study has shown that that retrospective LCMSMS analysis of newborn screening samples may not be appropriate as cortisol and 11-deoxycortisol are not stable in specimens undergoing long term storage at room temperature. 19 The prospective nature of this study was a strength, as it ensured the reliability of measured steroid parameters with no risk to screening sensitivity during the period of the study. However, this approach also limited the number of available samples from newborns with CAH to a relatively small number.…”
Section: Ta B L Ementioning
confidence: 99%
“…Further evaluation, over a much longer period, of this parameter is warranted if it is to be included in newborn screening protocols as retrospective studies are not possible because of the instability of 11DF in stored samples. 19 The incorporation of 21-deoxycortisol into newborn screening is gaining increasing attention. 22 21DF concentrations in this study however were not elevated in all specimens from newborns with confirmed CAH and 21DF was also detected in a small number of samples with a negative screening result.…”
Section: Ta B L Ementioning
confidence: 99%
“… LC-UV [ 78 ] (continued) Microsampling technique Matrix Analyte(s) Sample volume (μL) Analytical technique Reference DBS Blood Endogenous glucocorticoids 60 LC-MS/MS [ 79 ] VAMS Blood Endogenous glucocorticoids 10 LC-MS/MS [ 79 ] Noviplex (DPS) Plasma Endogenous glucocorticoids 40 LC-MS/MS [ 79 ] DBS Blood Endogenous glucocorticoids n.s. LC-MS/MS [ 80 ] DBS Blood Endogenous glucocorticoids n.s. LC-MS/MS [ 81 ] DBS Blood Endogenous glucocorticoids n.s.…”
Section: Microsampling and Sars-cov-2mentioning
confidence: 99%
“…In general, microsampling applications have been reported for endogenous corticosteroid determination (thus including cortisol and/or cortisone) in DBS [ [80] , [81] , [82] ] and in urine pretreated by SPME [ 83 , 84 ]. Regarding specifically the exogenous corticosteroids most often involved in SARS-CoV-2 therapy, budesonide has been analysed in DBS [ 85 ].…”
Section: Microsampling and Sars-cov-2mentioning
confidence: 99%